Sequential Myelomatous Pleural and Pericardial Effusions in Multiple Myeloma: A Case Report Demonstrating Extended Survival with Teclistamab - Deena Mudawi; Abdulrahman F. Al-Mashdali; Ahmad Tawalbeh; Lajos Szabados; Dina Sameh Soliman; Shehab Fareed (Case Reports in Oncology)
Introduction: Myelomatous pleural effusion (MPE) and pericardial involvement are rare manifestations of multiple myeloma (MM), occurring in less than 1% of cases and carrying historically poor prognoses. We present a unique case where both these rare serous cavity manifestations occurred sequentially in the same patient, demonstrating the evolving treatment landscape with novel targeted therapies. Case Presentation: A 42-year-old Asian female presented with left shoulder pain and swelling, leading to the diagnosis of IgG lambda MM with extensive extramedullary disease. After initial partial response to D-VRD therapy, she developed MPE with complete left lung collapse. Following failure of second-line KPD-PACE therapy, she received teclistamab, achieving complete metabolic and morphological response documented by PET-CT. After maintaining remission for 10 months, she experienced relapse with pericardial involvement presenting as cardiac tamponade. Conclusion: The patient demonstrated an unprecedented response to BCMA-targeted therapy with teclistamab, achieving complete remission that lasted 10 months – more than doubling the historical median survival of 4 months for MPE. Flow cytometry proved instrumental in rapid diagnosis, showing 11% lambda monotypic plasma cells in the pleural fluid. The subsequent pericardial involvement after initial complete response highlighted the persistent challenges in managing extramedullary disease. This case represents the first documented instance of sequential MPE and pericardial involvement in MM, demonstrating the potential of novel targeted therapies, particularly BCMA-directed approaches, in extending survival and improving outcomes in these rare but aggressive disease manifestations.